Secured services In cloud computing environment - Sahar Mohammed Abduljalil Abdullah; Ehab E. Hassanein; Osman Hegazy (Cairo : Sahar Mohammed Abduljalil Abdullah, 2014)
Securing services is always of vital importance and because of the critical nature of cloud computing and large amounts of complex data it carries, the need is even important. Cryptographic algorithms are one of the most important areas in security. They are sequences of processes, or rules, used to encipher and decipher messages in a cryptographic system. In simple terms, they're processes that protect data by making sure that unwanted people can't access it. Unfortunately, when the dataset size is huge, both memory use and computational cost can still be very expensive. In addition, single processor{u2019}s memory and CPU resources are very limited, which make the algorithm performance inefficient. The rapid advances in cloud computing has introduced a variety of security issues; each requires certain skills and knowledge. While developing business services requires conducting analysis and design for the business activities that does not include common security functions for these services
Thesis (M.Sc.) - Cairo University - Faculty of Computers and Information - Department of Information System
Issued also as CD
Keywords: Cloud Computing; Cloud computing services; Securing services